CHEMICAL AND STABLE ISOTOPIC COMPOSITIONS OF VOLATILES IN MANTLE PERIDOTITES OF THE YUSHIGOU OPHIOLITE IN QILIAN OROGENIC BELT, WESTERN CHINA - Hu P.Q.; Zhang M.J.; Tang Z.L.; Wang J.Z.; Li C.S. (My University, 2007)
Fluid inclusions in olivine and orthopyroxene of mantle peridotites from the Yushigou ophiolite can be divided into three types based on decrepitation temperature, shape and distribution. Type-1 fluid inclusions are characterized by oval or negative crystal shapes and small size (<5μm across). They occur in the cores and mantles of the host crystals, and decrepitated at > 840°C. Type-2 fluid inclusions have irregular or tabular shapes with relatively large size ( 10 - 100αm in length). They occur in irregular or circular healed micro-fractures in the host crystals, and decrepitated at 612 - 710°C. Type-3 fluid inclusions have size and shape similar to type-2 fluid inclusions but occur in micro-fractures restricted to the margins of the host crystals, and decrepitated at much lower temperature from 190°C to 340°C. The three different types of fluid inclusions are interpreted to represent primary, metasomatic (pseudo-secondary) and secondary inclusions, respectively. Stepwise heating reveals three concentration peaks of volatiles at 200 - 400°C, 400 - 800°C and 800 - 1200°C released from olivine and orthopyroxene in harzburgite and dunite from the Yushigou ophiolite, which are considered to correspond to the decrepitation of secondary, metasomatic and primary fluid inclusions at similar temperature ranges. CO2, is a major constituent in the volatiles released at three different temperature intervals. Trace amounts of H2, and N2, are present in the volatiles released at <800°C and trace amounts of H2O and SO2, are mainly present in the volatiles at 400 - 800°C. The δD (∼ 95.20‰, ∼ 306.3‰) of H2O and the δ 13C (∼ 15.5 ∼ 12.5‰) and δ 18O values (1.4 - 1.9‰) of CO2, released at < 800°C are lower than normal mantle values and suggest the mixing origin of crustal fluids (sedimentary organic) with ocean water, implying that Yushigou. AOLM had undergone an intensive metasomatism by a fluid composed of CO2, H2O and SO2, and followed by degassing. In contrast, the volatiles released at 800 - 1200°C are characterized by trace amounts of H2, and CO in dunite and SO2, in harzburgite, much lighter δ13 C (∼ 29.1‰ - ∼ 19.5‰), heavier δ13O (8.8‰) of CO2, and positive relationship between these isotopic ratios and the concentration of CO2. Such features can be best explained by mixing of significant terrestrial crustal (organic) and minor mantle volatiles. We proposed that the Yishigou peridotites are more likely to have derived from a continental lithosphere instead of an oceanic lithosphere comprising the Yishigou gabbros and pillowed basalts. A supra-subduction tectonic setting is thus inferred for the Yushigou ophiolite.
Keywords: FLUID INCLUSIONS; OPHIOLITE; PERIDOTITES; QILIAN OROGENIC BELT; STABLE ISOTOPES; VOLATILES